PENGGUNAAN APLIKASI DIGITAL OLEH PELAKU UMKM DI KOTA JAYAPURA PROVINSI PAPUA - Alfrida V.P Yamanop; Christine M. Wakarmamu; Omince Kobak (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2023)
This study aims to obtain an overview regarding the use of digital applications by MSMEs in Jayapura City, Papua Province. The approach of this study is qualitative and uses descriptive analysis in conveying the results of the data that has been obtained. The data in this study were obtained through observation, interviews, online questionnaires and literature review and other secondary data in accordance with the research theme. The results of the study show that in general the demographic, geographic and infrastructure conditions of Jayapura City support the existence of digital-based community activities for individuals, organizations, government and UMKM actors.